Komunikasi Antarbudaya dalam Kancah Global: Kompetensi Komunikasi Antarbudaya Pelajar Indonesia di Amerika - Naomi Uli Quanti Siahaan; Turnomo Rahardjo; Yanuar Luqman (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
In the era of globalization, competition and competition between countries is unavoidable. Every individual is competing to prepare themselves in global competition. Studying abroad is one of the chosen ways to equip oneself. However, in cultural activities there will be intercultural conflicts, culture shock, as evidenced by various cases, such as cases of resignation due to not being able to adapt to the new culture. Intercultural conflicts are also seen in the enthusiasm of Indonesian students to America which has decreased by 3.4%. This study aims to describe the intercultural communication of Indonesian students in America with a qualitative research method, which refers to the interpretive paradigm and phenomenological approach and uses in-depth interviews as a data collection technique. The theories used as a reference are the theory of Intercultural Communication Competence and Anxiety & Uncertainty Management. The results of the study revealed that the competence of the students who were characterized by motivation, knowledge and skills did not only talk about results and realization, but also about the process, from nothing to something and a little to more. It was called dynamic capabilities, where students are able to continue to move, accept and adapt to circumstances. All three were shown from before starting to starting college in America. Motivation was also not enough to carry out cross-cultural activities, but motivation to continue to communicate with other students and differences and new habits. And it doesn't stop at knowledge, the most important competency was the application of knowledge through and daily implementation with other people.